INVESTIGATION OF THE ANTITRYPANOSOMAL ACTIVITY OF BUCHHOLZIA CORIACEA SEED EXTRACT AGAINST A FIELD STRAIN OF TRYPANOSOMA CONGOLENSE - Nweze, Nwakaego Ernestina; Anene, Boniface Maduka; Asuzu, Isaac Uzoma (African Journal of Traditional, Complementary and Alternative Medicines, 2011)
The antitrypanosomal activity of the methanol extract of Buchholzia coriacea seed against a field strain of Trypanosoma congolense was investigated using experimentally infected mice of both sexes. Monitoring of parasitaemia was by the rapid matching technique. When parasitaemia was approximately log 7.8 (63 x 106 parasites/ml), treatment with graded doses of the extract (250, 500 and 1000 mg/kg) was instituted for 5 consecutive days. Diminazene diaceturate (DimivetÂ® SKM Pharma Pvt. Ltd.) was given at 3.5 mg/kg i.p. to the positive control mice. There was no significant difference between the PCV of the extract-treated and untreated animals. Three days post-treatment with diminazene diaceturate there was aparasitaemia however, a 50 % relapse rate was recorded in the same group later. The methanol extract of Buchholzia coriacea seeds showed no antitrypanosomal activity in mice infected with Trypanosoma congolense at the doses tested.